Venous Thromboembolic Events after Total Knee Arthroplasty: Which Patients Are at a High Risk? - Dai, Wen-Li; Lin, Ze-Ming; Shi, Zhan-Jun; Wang, Jian (The Journal of Knee Surgery, 2019)
Venous thromboembolism (VTE; deep venous thrombosis and pulmonary embolism) is a known complication following primary total knee arthroplasty (TKA). The aim of this study was to investigate the trends of the incidence of VTE after primary TKA and identify associated risk factors for the occurrence of VTEs in a large cohort of TKA patients. We performed a retrospective study in which the Nationwide Inpatient Sample (NIS) database was used to identify all patients who underwent primary TKA over a period of 13 consecutive years (between 2002 and 2014) in the United States. The occurrence of a symptomatic VTE was identified with the use of ICD-9-CM (International Classification of Diseases, Ninth Revision, Clinical Modification) diagnosis codes. A total of 1,460,901 primary TKA procedures were identified in the NIS from 2002 to 2014, and 12,944 of these patients were recorded as having 13,855 VTEs, consisting of 7,609 deep venous thromboses (0.52%) and 6,246 pulmonary emboli (0.43%). The overall VTE incidence in patients undergoing TKA in the United States from 2002 to 2014 was 0.89%. Patient-related risk factors for VTEs include an older age (odds ratio [OR]: 1.44; 95% confidence interval [CI]: 1.31–1.59), black race (OR: 1.34; 95% CI: 1.25–1.44), and Medicare insurance (OR: 1.18; 95% CI: 1.13–1.22). Most of the comorbidities were associated with an increased risk of VTE following TKA. Particularly, cardiac arrhythmias, coagulopathy, fluid and electrolyte disorders, pulmonary circulation disorders, and weight loss increased the risk of VTE by more than twofold. After adjusting for confounders, VTE was associated with a longer hospital stay (2.81 ± 0.02 day), increased costs (US$14,212.16 ± US$255.64), and higher mortality rate (OR: 13.04; 95% CI: 11.08–15.35). This nationally representative study of inpatients in the United States identified several independent risk factors for VTE perioperatively in TKA patients and provided evidence that VTE patients after TKA are likely to have worse results than non-VTE patients with regard to the length of hospital stay, hospital costs, and inhospital mortality. This is a level III, prognostic study.
Keywords: venous thromboembolic events; total knee arthroplasty; risk factors